(untitled) (The Conference Hub, 2025)
The purpose of writing this article is a holistic study of the life and scientific work of the Islamic reformer and modernist Sheikh Muhammad Abdo. To substantiate the thesis that M. Abdo’s modernism is a synthesis of Islam and modern thought. The socio-philosophical works of the thinker were aimed at uniting civilizations and overcoming contradictions and conflicts. To show that M. Abdo’s activities were multifaceted, he especially clearly showed his talent in the educational sphere, in reforming the system of higher religious education and journalism.